(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The proliferative phase of inflammation is the main stage of tissue repair and is characterized by the activation of cell proliferation, angiogenesis and the formation of extracellular matrix. The work discussed the mechanisms of the proliferative stage of inflammation, its connection with various diseases, and studied the development of new therapeutic approaches aimed at improving regenerative processes.